(x + 2)(3x + 1)
When the coefficient of the x² term is not 1 , then for a quadratic in standard form
That is ax² + bx + c (a ≠ 0) then to factor we consider the factors of the product ac which sum to give b
for 3x² + 7x + 2
the factors of the product 3 × 2 = 6 which sum to + 7 are + 6 and + 1
split the middle term using these factors
= 3x² + 6x + x + 2 → (factor by grouping )
= 3x(x + 2) + 1(x + 2) → (take out the common factor (x + 2))
= (x + 2)(3x + 1)
3x² + 7x + 2 =(x + 2)(3x + 1) ' in factored form '